Degradation of chitosan–gelatin and chitosan–gelatin–β-tricalcium phosphate scaffolds - Putri, Tansza Setiana; Pratiwi, Deviyanti; Margaretta, Dewi Liliany; Tjandrawinata, Rosalina; Shariff, Khairul Anuar (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Fabrication of the composite scaffold was carried out by combining chitosan, gelatin, and β-tricalcium phosphate (βTCP) derived from limestone. The extraction of βTCP was based on the abundance of limestone containing calcium carbonate, which can be a source of βTCP synthesis. Purpose: This study evaluates the degradation of the combination of chitosan–gelatin (ChG) and chitosan–gelatin–βTCP (ChG-βTCP) composite scaffolds. Methods: The freeze-drying method was used to obtain the composite scaffold, which was a mixture of chitosan, gelatin, and βTCP. Degradation was measured by immersing the samples in a simulated body fluid solution at 37°C for 3, 7, 14, and 21 days. For statistical analysis, one-way analysis of variance (ANOVA) and post hoc Fisher's least significant difference were performed. Results: The ChG scaffold shows better degradability than the ChG-βTCP scaffold. The ChG scaffold shows higher weight degradation than the ChG-βTCP scaffold up to 21 days. Conclusion: In conclusion, the scaffold containing βTCP has lower degradation than the ChG scaffold.